Strategi Pengelolaan Persediaan Barang pada UMKM Retail Bangunan: Sebuah Tinjauan Pustaka Sistematis - Syukria Resti Haq; Sakila Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Operational activities in the building retail business are greatly influenced by effective inventory management. Inventory that is not managed properly can cause shortages or excess stock which has an impact on increasing operational costs and disrupting service to customers. This study aims to analyze various inventory management strategies in building retail MSMEs through a literature review of various previous studies. The research method used is a systematic literature review by analyzing a number of scientific articles related to inventory management, the Economic Order Quantity (EOQ) method, inventory information systems, and inventory control strategies in MSMEs. The results of the study show that the application of inventory management strategies such as EOQ, safety stock, reorder points, classification of goods, and the use of inventory information systems can help improve operational efficiency and reduce the risk of shortages and excess inventory. Therefore, building retail MSMEs need to implement a more structured inventory management strategy so that business operations can run more effectively and efficiently.